(untitled) (Singapore,New Jersey, 2005)
This volume presents research results ranging from those in pure mathematical theory (semigroup theory, graph theory, etc.) to those in theoretical and applied computer science, e.g. formal languages, automata, codes, parallel and distributed computing, formal systems, knowledge systems and database theory.
Keywords: Information technology,Information science,Công nghệ thông tin,Khoa học thông tin; Mathematics,Mathematics,Toán học,Toán học